Study on Microstructure Differences of Coal Samples before and after Loading. (30th November 2020) - Liu, Jiajia; Fang, Yingxiang; Jia, Gaini; Chen, Shouqi; Hu, Jianmin
Abstract : The microscopic pore structure of coal affects the content of adsorbed gas. The microstructure of coal sample before and after loading is different, which will affect the adsorption and permeability of coal seam gas. In order to study this difference, the authors carried out mercury intrusion experiments on coal containing different coal samples and used nondestructive nuclear magnetic resonance (NMR) techniques, scanning electron microscopy, and transmission electron microscopy, to study the microstructure of coal samples before and after loading. The experimental results show that the pores of coal samples are mainly micropores and small pores, and the mesopores and macropores are relatively few. The T 2 spectrum area of the coal sample is significantly increased after loading, and the parallel-layer coal samples' T 2 spectrum area is 46735, which is 9112 more than the vertical layer coal samples. The T 2 spectrum of the vertical coalbed of saturated water samples shows a three-peak shape, the peak of the T 2 spectrum is 12692, and the parallel bedding shows a bimodal morphology. The peak area of the T 2 spectrum is 11277. The permeability of the parallel bedding coal sample is good, and the coal sample exhibits anisotropic properties. The pores and cracks of the coal samples increased after loading, and the localized area of the coal sample collapsed and formed a fracture zone, which was not conducive to the occurrence of coal seam gas. Further explanation of the changes in the permeability of the coal sample before and after loading will affect the gas storage and transportation.